1986
DOI: 10.1021/jo00355a026
|View full text |Cite
|
Sign up to set email alerts
|

Studies in sugar chemistry. 2. A simple method for O-deacylation of polyacylated sugars

Abstract: Decarbomethoxylation of Dimethyl [l-Phenyl-2(E)-butenyl]malonate (4). Decarbomethoxylation of 4 (71.6 mg, 0.273 mmol, [a]20!) +12°( c 1.0, chloroform), 30% ee), in a similar manner to that of 3, gave 31.4 mg (56%) of methyl [l-phenyl-2-(E)-butenyljacetate (7). [a]20D +1.1°( c 0.9, chloroform).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(39 citation statements)
references
References 0 publications
0
39
0
Order By: Relevance
“…The acylated carbohydrates studied present a variety of O-acyl groups whose reactivity depends on their position and configuration. In general, it is observed that the anomeric position was the first to be deacetylated due to the hemiacetal structure [24]. Based on this assumption we studied the selective anomeric deacetylation by the use of 1,2,3,4,6-penta-O-acetyl-a-D-glucopyranose as model compound (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The acylated carbohydrates studied present a variety of O-acyl groups whose reactivity depends on their position and configuration. In general, it is observed that the anomeric position was the first to be deacetylated due to the hemiacetal structure [24]. Based on this assumption we studied the selective anomeric deacetylation by the use of 1,2,3,4,6-penta-O-acetyl-a-D-glucopyranose as model compound (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 After subsequent Fmoc-deprotection using 20% piperidine in DMF, N 2 -terminal glycosylation was achieved by reaction with Gluc(4Ac)/S-1-heptaacetyl-cellobiosyl-mercaptopropionic acid pentafluorophenyl ester (1.1 eq) in the presence of N-ethyldiisopropylamine (1.1 eq). Dde deprotection of the Lys 5 side chain was performed using 2% hydrazine hydrate in DMF, followed by removal of the acetyl protecting groups in the sugar moiety using potassium cyanide in methanol (31). After final Boc-deprotection of the aminooxy-functionality using 50% TFA in dichloromethane (10 min), the peptides were purified using preparative RP-HPLC.…”
Section: Synthesis Of Small Organic Precursorsmentioning
confidence: 99%
“…Indeed,under Birch conditions [25a], the selective reduction of allylic alcohol of 1 by Li/NH 3 , permitted the obtainment of linaride (10-deoxyaucubin, 8) when the reaction was conducted at À78 C and 6,10-deoxyaucubin (9) when the reaction was conducted at À40 C [25]. In order to prepare 6-O-acetyllinaride (10), peracetyllinaride (11) [25b], quantitatively obtained from 8 by acetylation, was selectively deacetylated using a procedure initially described in the sugar chemistry and previously applied in our group to the selective deacetylation of peracetylaucubin [16,18,26]. Thus, treatment of 11 with a catalytic amount of potassium cyanide, in a 2:1 anhydrous mixture of CH 3 OH and CH 2 Cl 2 , for 3 h at 20 C, gave 10 in 48% yield, accompanied by fully deprotected linaride (8), which could be easily separated from the reaction mixture and recycled.…”
Section: Chemistrymentioning
confidence: 99%